2020
DOI: 10.1038/s41598-020-62145-1
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Foci in IDH1-mutated Gliomas Show STAT3 Phosphorylation and Downregulate the Metabolic Enzyme ETNPPL, a Negative Regulator of Glioma Growth

Abstract: IDH1-mutated gliomas are slow-growing brain tumours which progress into high-grade gliomas. The early molecular events causing this progression are ill-defined. Previous studies revealed that 20% of these tumours already have transformation foci. These foci offer opportunities to better understand malignant progression. We used immunohistochemistry and high throughput RNA profiling to characterize foci cells. These have higher pSTAT3 staining revealing activation of JAK/STAT signaling. they downregulate RnAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…This heterogeneity is also supported by two recent single cell RNA seq studies [21,22]. Additionally, we reported that approximately 20% of DLGG have transformation foci with cells showing a high level of activated STAT3 pathway and reduced level of a lipid metabolism enzyme, ETNPPL [23]. One consequence of this cellular heterogeneity is that current treatments may only target sub-populations of cells while leaving other cell types unaffected and prone to tumor relapse.…”
Section: Introductionsupporting
confidence: 64%
“…This heterogeneity is also supported by two recent single cell RNA seq studies [21,22]. Additionally, we reported that approximately 20% of DLGG have transformation foci with cells showing a high level of activated STAT3 pathway and reduced level of a lipid metabolism enzyme, ETNPPL [23]. One consequence of this cellular heterogeneity is that current treatments may only target sub-populations of cells while leaving other cell types unaffected and prone to tumor relapse.…”
Section: Introductionsupporting
confidence: 64%
“…Finally, overexpression of TGF-β-related protein Smad6 in nearly 90% of GBM tissues promotes the ubiquitination and subsequent degradation of the STAT3 inhibitor PIAS3 [ 41 , 42 , 43 ]. As a consequence of these aforementioned mechanisms, the reported frequency of phospho-Tyr-STAT3 positivity in human glioma samples ranges up to 60% and has been significantly correlated with histologic grade, EGFRvIII positivity, aggressive behavior, and poor prognosis [ 44 , 45 , 46 , 47 , 48 , 49 ]. Recent work has affirmed the negative prognostic significance of upregulation of JAK/STAT gene targets—e.g., cytokines, cytokine receptors, and JAKs—in the classical subtype of GBM [ 50 ].…”
Section: Biological Principles In Jak/stat Signaling In Glioblastomentioning
confidence: 99%
“…A prior report has linked MLC1 to the expression levels of another receptor tyrosine kinase, EGFR, in cultured astrocytes [ 39 ]. MLC1 has more recently been linked to EGFR signaling in low-grade human gliomas harboring R132H mutations in the IDH1 gene [ 40 ]. Hence, it is enticing to speculate the loss of MLC1 in GBM cells causes an imbalance in receptor tyrosine kinase expression and/or signaling, leading to a transition from a mesenchymal to an epithelial-like morphology with diminished growth and invasion.…”
Section: Discussionmentioning
confidence: 99%